Efek Lama Waktu Inkubasi Silase Isi Rumen Sapi Terhadap Kandungan Bahan Kering dan Organik serta Kecernaannya secara In Vitro - Atok, Julai Sisilia; Hilakore, Maritje A.; Lazarus , Edwin J. L.; Lawa, Emma D. Wie (Animal Agricultura, 2025)
This study aimed to analyze the effect of cattle rumen content silage (IRS) incubation duration on dry matter (DM) and organic matter (OM) content, as well as in vitro dry matter digestibility (DMD) and organic matter digestibility (OMD). The research was motivated by the potential of IRS as a nutritious alternative feed, which is constrained by its high moisture content (80-90%) and low palatability. The experimental method employed a Completely Randomized Design (CRD) with four incubation treatments (4, 6, 8, and 10 weeks) and four replications. The silage was formulated from a mixture of IRS (60%), rice bran (35%), palm sugar (5%), and 40 mL of Local Microorganisms (MOL: rumen fluid + young coconut water) as an activator. Digestibility was measured using the Tilley and Terry (1963) method, and statistical analysis was conducted with ANOVA followed by Duncan’s test. Results showed that 6 weeks of incubation (P2) reduced OM content by 12% (from 86.78% to 75.98%) while significantly increasing DMD (from 53.59% to 58.98%) and OMD (from 48.78% to 52.15%) (P<0.05). Prolonged incubation beyond 6 weeks (P3-P4) did not further improve digestibility due to substrate nutrient limitations. In conclusion, a 6-week incubation period optimizes in vitro IRS silage digestibility without excessive nutrient loss, demonstrating its potential as a sustainable feed processing strategy for livestock farming in arid regions.